2022
DOI: 10.1093/hr/uhab033
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance control of the scion by the rootstock under drought stress as revealed by transcriptome sequencing and mobile mRNA identification

Abstract: Grafting with pumpkin rootstock is commonly used not only to improve the quality of cucumber fruits but also to confer biotic or abiotic stress tolerance. However, the molecular mechanism of grafted cucumbers to drought stress and the possible roles of mobile mRNAs to improve stress tolerance have remained obscure. Hence, we conducted transcriptome sequencing and combined it with morpho-physiological experiments to compare the response of homografts (cucumber as scion and rootstock) (C) and heterografts (cucum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 81 publications
0
21
0
Order By: Relevance
“…This plant species is also one of the most popular rootstocks for cucurbit grafting, which has the ability to improve fruit quality [37], as well as stress tolerance [20,38,39]. In our previous study [40] we identified HSP70 as the stress-responsive mobile mRNA with a high expression level in response to drought stress in cucumber scion grafted onto pumpkin rootstock. Therefore, we selected this conserved gene family to perform a genome-wide analysis in pumpkin.…”
Section: Introductionmentioning
confidence: 99%
“…This plant species is also one of the most popular rootstocks for cucurbit grafting, which has the ability to improve fruit quality [37], as well as stress tolerance [20,38,39]. In our previous study [40] we identified HSP70 as the stress-responsive mobile mRNA with a high expression level in response to drought stress in cucumber scion grafted onto pumpkin rootstock. Therefore, we selected this conserved gene family to perform a genome-wide analysis in pumpkin.…”
Section: Introductionmentioning
confidence: 99%
“…The PIP1;2 was considered a candidate gene for improving the plant water conductivity in grafted hickory plants ( Kumar et al., 2018 ). Additionally, aquaporins were reported to be transported from pumpkin rootstocks to cucumber scions during drought ( Davoudi et al., 2022 ). Therefore, aquaporins and their related genes need further exploration in grafted plants under drought stress.…”
Section: Rootstock Changesmentioning
confidence: 99%
“…The Rubisco large subunit ( RbcL ), Rubisco small subunit ( RbcS ), chlorophyll a/b binding protein ( Cab ) and photosystem I p700 chlorophyll a apoprotein A2 ( psaB ) genes were up-regulated in chrysanthemum scions of the drought-resistant grafted plants and it helped maintain the photosynthetic performance ( Chen et al., 2018 ; Wilson and Hayer-Hartl, 2018 ). The movement of a series of mobile mRNAs from the pumpkin roots to the scions, also called scion-rootstock communication, can also improve the photosynthetic performance during drought conditions ( Davoudi et al., 2022 ). Specifically, multiple genes, including photosystem II CP47 reaction center protein ( psbB ), photosystem I p700 chlorophyll a apoprotein A2 ( psaB ), photosystem II protein D2 ( psbD ), photosystem I p700 chlorophyll a apoprotein A1 ( psaA ) and photosystem I light-harvesting chlorophyll a/b-binding protein ( LhcI ), functional in different photosynthesis-related processes, were induced to maintain the photosynthetic activity of the grafted plants ( Davoudi et al., 2022 ).…”
Section: Scion Changesmentioning
confidence: 99%
See 2 more Smart Citations